Direct-acting antivirals response in hepatocellular carcinoma: Does the presence of hepatocellular carcinoma matter? - Huang, Chung-Feng (Clin Mol Hepatol, 2019)
During the clinical trial development of directly acting antivirals (DAAs), evidence regarding the treatment efficacy in chronic hepatitis C patients with hepatocellular carcinoma (HCC) was scarce because these patients have always been excluded. Apart from the clinical trials, more HCC patients are currently being treated in daily practice, given that these treatments are highly effective and involve well-tolerated regimens. Large scale, real-world studies have demonstrated potentially suboptimal antiviral treatment efficacy in HCC patients who received DAAs. It is postulated that the impairment of the bioavailability of DAAs may account for the inferior treatment response. However, the results could not be generalized across all studies. The differing results were attributed to diverse patient characteristics, suboptimal regimens or imprecise definitions of active cancer statuses at the time of treatment initiation. Additional large-scale studies that utilize the treatment of choice in clearly defined HCC patients with different disease severities are warranted to clarify the issue.